Speech is silver, silence is golden - Ola Andersson; Hakan J. Holm (Games, 2013)
This paper experimentally investigates free-riding behavior on communication cost in a coordination game and finds strong indications of such free-riding. Firstly, the subjects wait for others to send a message when communication is costly, which does not happen when communication is costless. Secondly, the proportion of games where no communication or one-way communication takes place is much higher when communication is costly compared to when it is free.
Keywords: 330; free-riding; communication; coordination